Carotenoid pool of extremophilic bacterium Deinococcus radiodurans - Pokorná, Natálie (Jihočeská univerzita, 2021)
The thesis focuses on the carotenoid composition of the extremophilic bacterium D. radiodurans. The practical part of the thesis was focused on the composition of the carotenoid pool and the identification of the respective peaks of the chromatogram. Lastly, the influence of the age of the culture and exposure of the UV light was studied and evaluated.
Carotenoid pool of extremophilic bacterium Deinococcus radiodurans
Keywords: Deinococcus radiodurans; bacteria; carotenoids; HPLC; Deinococcus radiodurans; bacteria; carotenoids; HPLC